The Usage of Radio Streaming for Entrepreneurship Education - Monika Teguh; Patrisia Amanda Pascarina; Vincentius Jose Augusto (Journal on Education, 2023)
Entrepreneurship education is needed to encourage the growth of entrepreneurship in a country. Unfortunately, the pandemic has provided its own challenges in entrepreneurship learning. Therefore innovation is needed in learning methods, so that learning material can be conveyed properly, but still pay attention to the conditions of the students. In response, lecturers from the communication science department of Universitas Ciputra Surabaya, hereinafter referred to as UCS, developed a new learning method using radio streaming. UCS is a leading university in entrepreneurship learning, so this new method can be useful in developing entrepreneurship learning. With radio streaming, students can reach lessons easily and efficiently. This study aims to describe the practice of using radio streaming as a learning tool in entrepreneuship education. The approach used is qualitative, with case study method. Data collection was carried out by participatory observation method. The results of this study describe how entrepreneurship learning is done using radio streaming. There are two main activities with this method, namely learning entrepreneurship theory in the synchronous and asynchronous way, as well as direct entrepreneurship practice with features available on radio streaming. In addition, it also explains the advantages of what the students feel from this method of learning. It is hoped that the results of this research will be a real contribution to the world of entrepreneurship education.